Sanitation, hookworm, anemia, stunting, and wasting in primary school children in southern Ethiopia: Baseline results from a study in 30 schools - Grimes, Jack E. T. (PLoS Negl Trop Dis, 2017)
BACKGROUND: Inadequate nutrition; neglected topical diseases; and insufficient water, sanitation, and hygiene (WASH) are interrelated problems in schools in low-income countries, but are not routinely tackled together. A recent three-year longitudinal study investigated integrated school health and nutrition approaches in 30 government primary schools in southern Ethiopia. Here, we report on baseline associations between sanitation, hookworm infection, anemia, stunting, and wasting. METHODS: In each school, the Schistosoma mansoni, S. haematobium, and soil-transmitted helminth infection intensities; blood hemoglobin concentrations; heights; and weights of approximately 125 students were assessed. Of these 125 students, approximately 20 were randomly selected for student WASH surveys. Of these 20, approximately 15 were randomly selected for household sanitation observations. School WASH was also assessed through a combination of observations and questions to the headteacher. Mixed-effects logistic regression was used to compare household sanitation with hookworm infection (the other parasites being much less prevalent); and hookworm infection with anemia, stunting, and wasting. FINDINGS: Blood, stool, and urine samples were provided by 3,729 children, and student WASH and household WASH surveys were conducted with 596 and 448 of these students, respectively. Hookworm, Ascaris lumbricoides, Trichuris trichiura, and S. mansoni infections had prevalences of 18%, 4.8%, 0.6%, and 0.3%, respectively, and no S. haematobium infections were found. Anemia, stunting, and wasting had prevalences of 23%, 28%, and 14%, respectively. No statistically significant associations were found between latrine absence or evidence of open defecation at home, and hookworm infection (adjusted odds ratio, OR = 1.28, 95% confidence interval, CI: 0.476–3.44; and adjusted OR = 1.21, 95% CI: 0.468–3.12; respectively); or between hookworm infection and anemia, stunting, or wasting (adjusted OR = 1.24, 95% CI: 0.988–1.57; adjusted OR = 0.992, 95% CI: 0.789–1.25; and adjusted OR = 0.969, 95% CI: 0.722–1.30; respectively). CONCLUSIONS: In this setting, no statistically significant associations were found between sanitation and hookworm; or between hookworm and anemia, stunting, or wasting. More evidence on best practices for integrated school health interventions will be gathered from the follow-up surveys in this study.